Computational Comparison of the Uyghur and Turkish Grammar - Orhun, Murat; Tantug, A. Cueneyd; Adali, Esref; Soenmez, A. Coskun (IEEE, 2009)
This paper describes the differences between Uyghur (spoken in Sin Kiang, China) and Turkish Grammar on the sentence level. There are not many researches about natural language processing on Turkic languages except than Turkish. Uyghur language is one of the old and rich language in the Turkic language family. Even though both of these languages belong to the same language family, there are some important differences between them. Because of these reasons, it is not possible to implement a machine translation system between Uyghur and Turkish languages, which works on word by word translation simply. All of the words in the sentences must be analyzed at the morphologic level and define some translation rules, in order to avoid lost original sentence's mean. We hope this paper give some contribution for advanced studies to the Uyghur language in Machine Translation and Natural Language processing.
Keywords: Uyghur Morphology; Turkish Morphology; Machine Translation; Uyghur Grammar; Uyghur sentences; Computer Science